SIFAT KIMIA DAN FISIK TANAH SULFAT MASAM POTENSIAL SETELAH APLIKASI PUPUK LIMBAH CAIR PABRIK KELAPA SAWIT - Ida Nursanti (Universitas Batanghari Jambi, 2015)
Exploiting the potential acid sulphate soils for agriculture are faced with soil chemical properties that are less supportive include low pH; levels of Al, Fe, Mn and SO4 high; high salt content; macro nutrient deficiency. It is necessary for the palm oil mill effluent (POME) that can be used as organic fertilizer. The study aims to determine the effect of incubation fertilizer palm oil mill effluent to an anaerobic secondary first time retaining hydrolysis of 4 weeks against chemical and physical properties of acid sulfate soil and determine fertilizer palm oil mill effluent to an anaerobic secondary first time retaining hydrolysis 4 weeks right. The research was conducted at PT. Sumbertama Nusa Pertiwi Kumpeh District of Ulu Muaro Jambi and in the laboratory, lasted for 3 months. Research using completely randomized design , with 3 levels of treatment provision of secondary anaerobic pond POME first with a time of 4 weeks detention hydrolysis, incubated at 10 kg a potential acid sulphate soil. The treatments studied 500, 750 and 1000 ml polybag-1. The results showed that administration of an anaerobic POME first secondary effect on the physical and chemical properties of acid sulphate soil. Giving POME1000ml provide better value.Keywords : Acid sulfated soil, POME